Understanding Classroom Activities in Speaking Courses in College: A Case Study in the Post-Pandemic Era - Ulayya, Nadiya Kaltsum; Anggraini, Hesti Wahyuni (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
Classroom activities are crucial in speaking courses as they significantly influence students' speaking abilities. It is imperative for lecturers to employ appropriate activities tailored to student needs. This study aims to investigate the classroom activities utilized by a lecturer in a